Studi Penanganan Kawasan Permukiman Kumuh Di Desa Senga Selatan Kecamatan Belopa Kabupaten Luwu - Syam, Esse; Syafri, Syafri; Margolang, Syamsuddin (Journal of Urban Planning Studies, 2024)
Slums area settlements that are unfit for habitation because of the irregularity of the buildings, the high level of building density, and the quality of the buildings and facilities and infrastructure that do not meet the requirements. Luwu Regency is one of the areas that has a slum location located in Senga Selatan Village. In the context of handling slum areas, identification is carried out to determine the level of slums, the determinant factors that affect the level of slums and the handling of slum areas. Identification is carried out using an analysis of the level of slums based on the 2018 PUPR Ministerial Regulation. The implementation is carried out based on survey data results, an analysis of the calculation of the slum level scoring assessment, and range values. From the results of the analysis it is known that Senga Selatan Village is included in mild slums, the determinant factors that cause slums are from the aspect of building conditions, environmental drainage conditions, and fire protection conditions.